1997
DOI: 10.1007/bf01808876
|View full text |Cite
|
Sign up to set email alerts
|

Muslin induced granuloma following wrapping of intracranial aneurysms: The role of infection as an additional precipitating factor

Abstract: Two patients who developed what appeared to be a granulomatous reaction following muslin wrapping of unclipped aneurysms are reported. They presented with cranial nerve palsies and at operation were found to have an abscess around the wrapped aneurysms. In one of these two patients Staphylococcus epidemidis was isolated from the pus. This, together with further evidence from reported cases in the literature, would suggest that infection may play an additional role at least in some cases in the onset of a forei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 10 publications
2
20
0
Order By: Relevance
“…Although the presence of foreign material can initiate a foreign body granulomatous reaction it is not understood why some patients are affected and others not (Chambi et al, 1990;Kirollos et al, 1997). Considering the large number of different materials used in neurosurgery, deliberately introduced into the central nervous system and left insitu, only a small number of patients will present with complications, either early or late (Feldman et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Although the presence of foreign material can initiate a foreign body granulomatous reaction it is not understood why some patients are affected and others not (Chambi et al, 1990;Kirollos et al, 1997). Considering the large number of different materials used in neurosurgery, deliberately introduced into the central nervous system and left insitu, only a small number of patients will present with complications, either early or late (Feldman et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…A Medline search of the literature published until December 2011, using subject heading “intracranial postoperative granuloma,” produced only 42 results. Most of these articles describe aseptic foreign body granuloma formation caused by a variety of substances including gel foam [3], surgical swab [4], bone wax [5], cotton pledgets [6, 7], rayon [8], suture [9], oxidized cellulose [10], microfibrillar collagen [11], muslin gauze [12], and polytetrafluoroethylene [13]; some others refer also to infectious granulomas secondary to aneurism surgery [14] or gasserian ganglion decompression [15]. Furthermore, intracranial granulomas not related to previous neurosurgical procedures may have a tumor-like origin, as in case of plasma cell granulomas [16] and neurosarcoidosis [17], or infectious aetiology, associated or not with extracranial localizations, generally due to fungal [18] or acid-fast organisms [19].…”
Section: Discussionmentioning
confidence: 99%
“…A number of materials have been used to treat aneurysms : muslin gauze 10,17) , surgicel, muscle 5,14) , biobond adhesive, and histoacryl adhesive 2) . In an early study, a high rebleeding rate was reported when biobond was used as a coating agent 11) .…”
Section: Discussionmentioning
confidence: 99%
“…Muslin gauze is regarded as an effective material by inducing fibrosis which reinforces the aneurysm sac, and possibly inducing intraluminal thrombosis 6,14) . On the other hand, it has caused foreign body reaction such as infection or granuloma 8,10) . It can also cause cranial nerve injury, especially to the optic or oculomotor nerve in anterior circulation and brain edema, which causes chronic headache or mental deterioration 1,13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation